Dietary n-3/n-6 polyunsaturated fatty acid ratio modulates growth performance in spotted seabass (Lateolabrax maculatus) through regulating lipid metabolism, hepatic antioxidant capacity and intestinal health - Dong, Yanzou; Wei, Yu; Wang, Ling; Song, Kai; Zhang, Chunxiao; Lu, Kangle; Rahimnejad, Samad (Animal nutrition (Zhongguo xu mu shou yi xue hui), 2023)
An 8-week feeding experiment was carried out to explore the effects of dietary n-3/n-6 polyunsaturated fatty acid (PUFA) ratio on growth performance, lipid metabolism, hepatic antioxidant status, and gut flora of spotted seabass (Lateolabrax maculatus). Six experimental diets were formulated to contain different levels of two purified oil sources including docosahexaenoic and eicosapentaenoic acids enriched oil (n-3) and linoleic acid-enriched oil (n-6) leading to n-3/n-6 PUFA ratios of 0.04, 0.35, 0.66, 1.35, 2.45 and 16.17. Each diet was fed to triplicate groups of juvenile L. maculatus (11.06 ± 0.20 g, 30 fish/tank). Final body weight (FBW), weight gain (WG), specific growth rates (SGR), protein efficiency ratio (PER) and feed utilization efficiency increased as n-3/n-6 PUFA ratio increased up to a certain level, and then decreased thereafter. Fish fed the diet with n-3/n-6 PUFA ratio of 0.66 exhibited the highest FBW, WG, SGR and PER and the lowest feed conversion ratio. Lower n-3/n-6 PUFA ratios induced up-regulated expression of lipid synthesis-related genes (fas, acc2 and srebp-1c) and down-regulated expression of lipolysis related genes (atgl, pparα, cpt-1 and aox). Higher expression of lipolysis-related genes (atgl, pparα and cpt-1) was recorded at moderate n-3/n-6 PUFA ratios (0.66 to 1.35). Moreover, inappropriate n-3/n-6 PUFA ratios triggered up-regulation of pro-inflammatory genes (il-6 and tnf-α) and down-regulation of anti-inflammatory genes (il-4 and il-10) in the intestine. The diet with n-3/n-6 PUFA ratio of 0.66 inhibited intestine inflammation, improved intestinal flora richness, increased the abundance of beneficial bacteria such as Lactobacillus, Alloprevotella and Ruminococcus, and reduced the abundance of harmful bacteria including Escherichia-Shigella and Enterococcus. In summary, it could be suggested that a dietary n-3/n-6 PUFA ratio of 0.66 can improve growth performance and feed utilization in L. maculatus, as is deemed to be mediated through regulation of lipid metabolism and intestinal flora.
Keywords: Growth performance; Lateolabrax maculatus; n-3/n-6 PUFA ratio; Intestinal flora; Lipid metabolism